Energy Requirements for Maintenance and Growth of Male Saanen Goat Kids - Medeiros, A. N. (2014)
The aim of study was to determine the energy requirements for maintenance and growth of forty-one Saanen, intact male kids with initial body weight (BW) of 5.12 +/- 0.19 kg. The baseline (BL) group consisted of eight kids averaging 5.46 +/- 0.18 kg BW. An intermediate group consisted of six kids, fed for ad libitum intake, that were slaughtered when they reached an average BW of 12.9 +/- 0.29 kg. The remaining kids (n = 27) were randomly allocated into nine slaughter groups (blocks) of three animals distributed among three amounts of thy matter intake (DMI; ad libitum and restricted to 70% or 40% of ad libitum intake). Animals in a group were slaughtered when the ad libitum-treatment kid in the group reached 20 kg BW. In a digestibility trial, 21 kids (same animals of the comparative slaughter) were housed in metabolic cages and used in a completely randomized design to evaluate the energetic value of the diet at different feed intake levels. The net energy for maintenance (NEm) was 417 kJ/kg(0.75) of empty BW (EBW)/d, while the metabolizable energy for maintenance (MEm) was 657 kJ/kg(0.75) of EBW/d. The efficiency of ME use for NE maintenance (k(m)) was 0.64. Body fat content varied from 59.91 to 92.02 g/kg of EBW while body energy content varied from 6.37 to 7.76 MJ/kg of EBW, respectively, for 5 and 20 kg of EBW The net energy for growth (NE,) ranged from 7.4 to 9.0 MJ/kg of empty weight gain by day at 5 and 20 kg BW, respectively. This study indicated that the energy requirements in goats were lower than previously published requirements for growing dairy goats.